New clues to organ size control in plants - Bögre, László (BioMed Central, 2008)
Plant growth has unparalleled importance for human civilization, yet we are only starting to gain an understanding of its mechanisms. The growth rate and final size of plant organs is determined by both genetic constraints and environmental factors. Regulatory inputs act at two control points: on proliferation; and on the transition between proliferation and differentiation. Cell-autonomous and short-range growth signals act within meristematic domains, whereas diffusible signals from differentiated parts to proliferating cells provide measures of geometry and size and channel environmental inputs.